THE EFFECT OF BIOPHILIC ON THE DESIGN OF SMART AQUAPONIC APARTMENTS IN SURABAYA - sigit firdaus prayogi; Yazid Yazid (Gestalt : Jurnal Desain Komunikasi Visual, 2021)
Urban people who have high mobility are starting to realize the importance of better environmental health by reducing air pollution so that they can reduce high stress levels. Being in the house, does not mean avoiding air pollution. According to the EPA (US Environmental Protection Agency) or environmental protection agency in the United States, indoor air pollution is 2-5 times greater than outdoors. Then came the biophilic trend for urban communities by making their homes a comfortable and healthy place by using live plants as a lifestyle because they nourish the body both physically and psychologically. Limited residential areas such as apartments are starting to become the choice of urban communities because of good security, complete facilities, and easy parking and strategic locations. The problem of small residential land in apartments is a problem for users, so they tend to choose to use multifunctional products. The limited land also makes it difficult for the residents to channel their hobby of maintaining plants and pets, as a means of recreation and entertainment. Researchers try to analyze the need for multifunctional furniture that can channel the hobby of raising animals and plants, namely Smart Aquaponics; by not taking up a large space, having an attractive design and complete with automation features. This smart aquaponics research was conducted for apartment users who need a good living environment but have limited time to maintain it. This study tries to apply an automation system in Smart Aquaponik products that can help apartment residents to be able to have functional furniture that accommodates a biophilic lifestyle.